Repeatable Territorial Aggression in a Neotropical Poison Frog - Chaloupka, Sarah; Peignier, Mélissa; Stückler, Susanne; Araya-Ajoy, Yimen; Walsh, Patrick; Ringler, Max; Ringler, Eva (Frontiers in Ecology and Evolution, 2022)
Intra-specific aggressive interactions play a prominent role in the life of many animals. While studies have found evidence for repeatability in boldness, activity, and exploration in amphibians, we know relatively little about consistent among-individual variation in aggressiveness, despite its importance for male-male competition and territoriality. Amphibians, and Neotropical poison frogs (Dendrobatidae) in particular, are highly suitable for investigating among-individual variation in aggressiveness, as most species exhibit strong territoriality in at least one of the sexes. In the present study, we aimed to fill this gap in knowledge, by investigating within- and between-individual variation in territorial aggression in a semi-natural population of the Neotropical poison frog Allobates femoralis (Dendrobatidae) in French Guiana. We conducted repeated, standardized behavioral tests to assess if the level of territorial aggression is consistent within and different between individuals. Further, we tested a possible link between body size and level of territorial aggression. We found moderate repeatability in territorial aggressiveness, but no link to age and/or body size. In conclusion, our study represents the first documentation of repeatable aggressive behavior in a territorial context in amphibians.